2018
DOI: 10.5194/isprs-annals-iv-2-9-2018
|View full text |Cite
|
Sign up to set email alerts
|

Bundle Adjustment-Based Stability Analysis Method With a Case Study of a Dual Fluoroscopy Imaging System

Abstract: A fundamental task in photogrammetry is the temporal stability analysis of a camera/imaging-system’s calibration parameters. This is essential to validate the repeatability of the parameters’ estimation, to detect any behavioural changes in the camera/imaging system and to ensure precise photogrammetric products. Many stability analysis methods exist in the photogrammetric literature; each one has different methodological bases, and advantages and disadvantages. This paper presents a simple and rigorous stabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…If changes of the camera geometry occur due to temperature changes, it is important to estimate the impact at measurements in 3D object space [36][37][38]. The Monte-Carlo simulation was used to evaluate how different changes of the camera geometry affect errors in object space.…”
Section: Simulating the Impact Of Differently Changing Iop At Measurementioning
confidence: 99%
See 1 more Smart Citation
“…If changes of the camera geometry occur due to temperature changes, it is important to estimate the impact at measurements in 3D object space [36][37][38]. The Monte-Carlo simulation was used to evaluate how different changes of the camera geometry affect errors in object space.…”
Section: Simulating the Impact Of Differently Changing Iop At Measurementioning
confidence: 99%
“…Therefore, sets of k (k ∈ N) parameters, reflecting the IOP, are randomly generated n-times (n ∈ N) considering residuals and mathematically correlations, to project n regular grids of image points onto a virtual object plane in 3D object space. As indicated by [36,38], IOP-related variations in object space are highly correlated with the reference object that is used for intersection and "should be as close as possible to the expected object products of the photogrammetric application of interest" [36]. If this is not considered, more degrees of freedom related to the object scene are introduced that might mitigate or intensify IOP-related variations due to depth variations of the reference object.…”
Section: Simulating the Impact Of Differently Changing Iop At Measurementioning
confidence: 99%
“…In practice, steps 2) and 3) are often combined, resulting in a two-step procedure: 1) correction of image distortion; and 2) 3D space calibration [22]- [24]. In recent years, all three steps are combined into a unified optimization process to account for the parameter correlations that exist between the steps [14], [15], [25]. While there are certain benefits of doing a single optimization (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…There are incentives for achieving an accurate calibration with reduced data (i.e. by using less time to acquire and process the data); for example, more imaging time can be allocated to patients, or the fluoroscope can be calibrated more frequently to ensure its optimal performance ( [15] suggested that fluoroscopic systems may exhibit submillimeter 3D changes in measurement error over the course of a day).…”
mentioning
confidence: 99%